2002
DOI: 10.1002/yea.846
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional analysis of a MIG1 homologue from the yeast Schwanniomyces occidentalis

Abstract: A putative glucose repressor MIG1-homologue (SoMIG1) was isolated from the amylolytic yeast Schwanniomyces occidentalis. Degenerate primers were designed from the conserved zinc finger regions of Mig1 and CreA proteins from different organisms. PCR using these primers and S. occidentalis genomic DNA as template yielded a single 128 bp product. This fragment was used as a DNA probe to screen a S. occidentalis genomic library. Analysis of the positive clones led to the isolation by PCR of a DNA fragment, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…A search in the H. polymorpha genome database (Ramezani‐Rad et al , 2003) revealed the presence of two putative homologues of S. cerevisiae Mig1 (ScMig1) C2H2 zinc‐finger (ZnF) transcriptional repressor (Nehlin & Ronne, 1990). Similar results were obtained after probing the genome database with full‐length ScMig1, or its N‐terminal ZnF DNA‐binding domain, which is highly conserved in all yeast Mig1 homologues (Ostling et al , 1996; Cassart et al , 1997; Zaragoza et al , 2000; Carmona et al , 2002), or the full‐length sequence of the related S. cerevisiae Mig2 protein (Lutfiyya & Johnston, 1996). As expected, the two identified H. polymorpha Mig1 homologues, designated as HpMig1 and HpMig2 , exhibit limited overall homology to other yeast Mig proteins: for instance, 26% identity and 41% similarity to ScMig1; 32% identity and 43% similarity to Candida albicans Mig1 (Zaragoza et al , 2000); and 34% identity and 45% similarity to Schwanniomyces occidentalis Mig1 (Carmona et al , 2002).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…A search in the H. polymorpha genome database (Ramezani‐Rad et al , 2003) revealed the presence of two putative homologues of S. cerevisiae Mig1 (ScMig1) C2H2 zinc‐finger (ZnF) transcriptional repressor (Nehlin & Ronne, 1990). Similar results were obtained after probing the genome database with full‐length ScMig1, or its N‐terminal ZnF DNA‐binding domain, which is highly conserved in all yeast Mig1 homologues (Ostling et al , 1996; Cassart et al , 1997; Zaragoza et al , 2000; Carmona et al , 2002), or the full‐length sequence of the related S. cerevisiae Mig2 protein (Lutfiyya & Johnston, 1996). As expected, the two identified H. polymorpha Mig1 homologues, designated as HpMig1 and HpMig2 , exhibit limited overall homology to other yeast Mig proteins: for instance, 26% identity and 41% similarity to ScMig1; 32% identity and 43% similarity to Candida albicans Mig1 (Zaragoza et al , 2000); and 34% identity and 45% similarity to Schwanniomyces occidentalis Mig1 (Carmona et al , 2002).…”
Section: Resultssupporting
confidence: 73%
“…for instance, 26% identity and 41% similarity to ScMig1; 32% identity and 43% similarity to Candida albicans Mig1 (Zaragoza et al, 2000); and 34% identity and 45% similarity to Schwanniomyces occidentalis Mig1 (Carmona et al, 2002). However, in the region of N-terminal ZnF domains, the similarity is high: 80% and 76% identity to ScMig1 for HpMig1 and HpMig2, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…4). The above‐mentioned DNA binding zinc finger domain is strongly conserved among the Mig1 homologues of different yeasts [29,32]. Thus, we hypothesize that homologues of the MAL activator and Mig1 proteins may exist in H. polymorpha .…”
Section: Resultsmentioning
confidence: 88%
“…According to the literature, transcriptional regulators of maltase genes from other yeasts can function in S. cerevisiae . For example, the Mig1 repressor homologues from Candida utilis [27], K. lactis [28] and Schwanniomyces occidentalis [29] complement the Mig1 deficiency in S. cerevisiae , and the MAL activator of C. albicans (CASUC1) can substitute the function of MAL63 activator protein in S. cerevisiae [30]. We inspected the GenBank data resulting from the partial genomic sequencing project of H. polymorpha [31] in order to find nucleotide sequences that might encode homologues of S. cerevisiae MAL activator and Mig1 repressor proteins.…”
Section: Resultsmentioning
confidence: 99%